Safety and efficacy of PfSPZ Vaccine against Plasmodium falciparum via direct venous inoculation in healthy malaria-exposed adults in Mali: a randomised, double-blind phase 1 trial. Issue 5 (May 2017) - Sissoko, Mahamadou S; Healy, Sara A; Katile, Abdoulaye; Omaswa, Freda; Zaidi, Irfan; Gabriel, Erin E; Kamate, Bourama; Samake, Yacouba; Guindo, Merepen A; Dolo, Amagana; Niangaly, Amadou; Niaré, Karamoko; et al.
Summary: Background: Plasmodium falciparum sporozite (PfSPZ) Vaccine is a metabolically active, non-replicating, whole malaria sporozoite vaccine that has been reported to be safe and protective against P falciparum controlled human malaria infection in malaria-naive individuals. We aimed to assess the safety and protective efficacy of PfSPZ Vaccine against naturally acquired P falciparum in malaria-experienced adults in Mali. Methods: After an open-label dose-escalation study in a pilot safety cohort, we did a double-blind, randomised, placebo-controlled trial based in Donéguébougou and surrounding villages in Mali. We recruited 18–35-year-old healthy adults who were randomly assigned (1:1) in a double-blind manner, with stratification by village and block randomisation, to receive either five doses of 2·7 × 10 5 PfSPZ or normal saline at days 0, 28, 56, 84, and 140 during the dry season (January to July inclusive). Participants and investigators were masked to group assignments, which were unmasked at the final study visit, 6 months after receipt of the last vaccination. Participants received combined artemether and lumefantrine (four tablets, each containing 20 mg artemether and 120 mg lumefantrine, given twice per day over 3 days for a total of six doses) to eliminate P falciparum before the first and last vaccinations. We collected blood smears every 2 weeks and during any illness for 24 weeks after the fifth vaccination. The primary outcome was the safety and tolerability of the vaccine, assessed as local and systemic reactogenicity and adverse events. The sample size was calculated for the exploratory efficacy endpoint of time to first P falciparum infection beginning 28 days after the fifth vaccination. The safety analysis included all participants who received at least one dose of investigational product, whereas the efficacy analyses included only participants who received all five vaccinations. This trial is registered atClinicalTrials.gov, numberNCT01988636 . Findings: Between Jan 18 and Feb 24, 2014, we enrolled 93 participants into the main study cohort with 46 participants assigned PfSPZ Vaccine and 47 assigned placebo, all of whom were evaluable for safety. We detected no significant differences in local or systemic adverse events or laboratory abnormalities between the PfSPZ Vaccine and placebo groups, and only grade 1 (mild) local or systemic adverse events occurred in both groups. The most common solicited systemic adverse event in the vaccine and placebo groups was headache (three [7%] people in the vaccine group vs four [9%] in the placebo group) followed by fatigue (one [2%] person in the placebo group), fever (one [2%] person in the placebo group), and myalgia (one [2%] person in each group). The exploratory efficacy analysis included 41 participants from the vaccine group and 40 from the placebo group. Of these participants, 37 (93%) from the placebo group and 27 (66%) from the vaccine group developed P falciparum infection. The hazard ratio for vaccine efficacy was 0·517 (95% CI 0·313–0·856) by time-to-infection analysis (log-rank p=0·01), and 0·712 (0·528–0·918) by proportional analysis (p=0·006). Interpretation: PfSPZ Vaccine was well tolerated and safe. PfSPZ Vaccine showed significant protection in African adults against P falciparum infection throughout an entire malaria season. Funding: US National Institutes of Health Intramural Research Program, Sanaria.